Social Commerce Surge: The Fusion of Shopping and Social Media - Aditya Pandowo; Shinta Rahmani; Ajeng Andriani Hapsari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study investigates the dynamics of social commerce within PT. Manado Jaya Lestari, focusing on the influence of Social Media Engagement and E-commerce Features on Consumer Trust and Purchasing Behavior. A sample of 100 consumers was selected through random sampling, and data were collected via structured surveys. The analysis was conducted using Smart PLS (Partial Least Squares) to examine both direct and indirect effects. The results reveal that Social Media Engagement significantly influences Consumer Trust and Purchasing Behavior, both directly and indirectly. However, while E-commerce Features demonstrates a significant direct effect on Purchasing Behavior, its indirect effect through Consumer Trust is nonsignificant. These findings underscore the crucial role of consumer trust as a mediator in the relationship between social media engagement and purchasing behavior. The study concludes by emphasizing the importance of fostering consumer trust through active engagement on social media platforms to drive sales, alongside continually improving e-commerce features to enhance the overall online shopping experience. Keywords : Social Media Engagement , E-commerce Features, Consumer Trust, Purchasing Behavior